Precarious Migrancy, Community, and Resilience in Debendranath Acharya’s Jangam - Binayak Roy (Asiatic: IIUM Journal of English Language and Literature, 2023)
Literary narrative provides a new perspective of looking at the historical past, often questioning the credibility of representation. Interrogating what Hayden White calls history’s tropic prefiguration, the prominence given to key historical figures, the erasure of subaltern individuals or communities, literature foregrounds the role of narrative in constructing the way one understands the world, meaning, and truth. A postcolonial writer, in their critical re-interpretation of the historical archive, creates a hybrid text that combines historical evidences and imaginative reconstructions, and historical as well as invented characters. With this interplay, history is stripped of its objective quality. This article seeks to explore how Debendranath Acharya’s Jangam presents the precarious condition of the migrant Burmese Indian peasants during World War II and the manner in which they establish a community during their historically forgotten long march to Assam. What Acharya attempts to reconcile in Jangam are the “analytical” histories through utilising the rational categories of modern historical thought and the “affective” histories which account for the plural ways of being-in-the-world.